Polyvalent Bacterial Lysate Protects Against Pneumonia Independently of Neutrophils, IL-17A or Caspase-1 Activation - Ferrara, Florencia; Rial, Analía; Suárez, Norma; Chabalgoity, José Alejandro (Frontiers in Immunology, 2021)
Polyvalent bacterial lysates have been in use for decades for prevention and treatment of respiratory infections with reported clinical benefits. However, besides claims of broad immune activation, the mode of action is still a matter of debate. The lysates, formulated with the main bacterial species involved in respiratory infections, are commonly prepared by chemical or mechanical disruption of bacterial cells, what is believed influences the biological activity of the product. Here, we prepared two polyvalent lysates with the same composition but different method of bacterial cell disruption and evaluated the basis of their biological activity in a comparative fashion. We found that bacterial lysates induce NF-kB activation in a MyD88 dependent manner, suggesting they work as TLR agonists. We have previously shown that prior S. pneumoniae sub lethal infection or therapeutic treatment with a TLR5 agonist both induce protection against pneumococcal pneumonia. Protection depends on neutrophil recruitment to the lungs, and can be associated with increased local expression of IL-17A. Here, we show that bacterial lysates exert protection against pneumococcal pneumonia independently of neutrophils, IL-17 orCaspase-1/11 activation, suggesting the existence of redundant mechanisms of protection. Trypsin-treated lysates afford protection to the same extent, suggesting that just small peptides suffice to exert the protective effect or that the molecules responsible for the protective effect are not proteins. Understanding the mechanism of action of bacterial lysates and deciphering the active components shall allow redesigning them with more precisely defined formulations and expanding their range of action.